Qualitative study exploring the key determinants of information gathering to inform the management of over-the-counter (OTC) consultations in community pharmacies. Issue 8 (15th August 2019) - Cassie, Heather; Duncan, Eilidh M; Gibb, Elizabeth A; Power, Ailsa; Young, Linda; Newlands, Rumana; Watson, Mags C
Abstract : Objectives: Gathering relevant patient information during over-the-counter (OTC) consultations increases the likelihood of safe, effective and person-centred outcomes. The aim of this study was to explore the key determinants to information gathering during consultations for non-prescription medicine requests in community pharmacies in Scotland. Design: Semi-structured interviews using the Theoretical Domains Framework (TDF), with community pharmacy teams across Scotland. Interviews explored participants' knowledge of current guidance, skills required to elicit information and barriers and facilitators associated with this behaviour. Theory-based content analysis was undertaken using the TDF as an initial coding framework to identify key determinants and map them to salient domains. Salience was determined by prominence or variation in views. Comparative analysis was undertaken by professional role. Results: Thirty interviews were conducted with pharmacists (n=19) and medicine counter assistants (MCAs) (n=11). Eight salient domains were identified: environmental context and resources (privacy), beliefs about consequences (patient safety), skills (communication, decision-making), social influences (patient awareness of pharmacist role), knowledge (awareness and use of standard operating procedures), social professional role and identity (perception of own role), behavioural regulation (training) and intention (to gather information). Similar domains were salient for pharmacists and MCAs; however, different beliefs were associated with different roles. Overarching themes were identified: best practice, health literacy, decision-making and professionalism. Conclusions: Multiple influences and complexities affect the effective management of OTC consultations. While similar factors impact on both pharmacists and MCAs at a patient, professional and environmental level, subtle differences exist in how these influence their management of OTC consultations. This study highlights the importance of tailoring interventions to reflect different roles, functions and responsibilities of community pharmacy personnel.